(untitled) (Dentika: Dental Journal, 2011)
Erythema multiforme is an acute vesiculo-bullous disease on the skin and membrane mucous, self limiting, and it presents with clinical variation (multiforme). Patients who suffer EM will feel painful of the oral lesion, wich could interfere in intaking of food and nutrition, and further more can bring down the body resistance. Approximatelly 50% case of EM caused by medicamen hiperensitivity reaction, most often because the class of sulfonamide drugs, NSAIDs, and anticonvulsants. A male patient aged 41 years, suffering of painful blisters with spontaneous bleeding on the mouth, difficulty in eating and talking. Patient was taking carbamazepine and amitriptyline given by neurologist. Patient also finished taking amoxicillin provided by dentist two days ago. Extra oral shows erosion and ulcers, painful and easily bleeding on the red upper and lower lips. Most ulcers were covered by erythematous-brown crust. Intra oral showed erosion/ ulcers, painful, easily bleeding, and covered by yellow-white pseudomembrane. There were no abnormalities on the skin. In conclusion to stop using all drugs that suspected as the cause, systemic corticosteroid administration, topical anesthesia, supportive therapy, and education for patient responded positively to patient’s recovery.